An in Vivo Mouse Model to Investigate the Effect of Local Anesthetic Nanomedicines on Axonal Conduction and Excitability - Moldovan, Mihai; Alvarez, Susana; Rothe, Christian; Andresen, Thomas L.; Urquhart, Andrew; Lange, Kai H. W.; Krarup, Christian (Frontiers in Neuroscience, 2018)
Peripheral nerve blocks (PNBs) using local anaesthetic (LA) are superior to systemic analgesia for management of post-operative pain. An insufficiently short PNB duration following single-shot LA can be optimized by development of extended release formulations among which liposomes have been shown to be the least toxic. In vivo rodent models for PNB have focused primarily on assessing behavioural responses following LA. In a previous study in human volunteers we found that it is feasible to monitor the effect of LA in vivo by combining conventional conduction studies with nerve excitability studies. Here we aimed to develop a mouse model where the same neurophysiological techniques can be used to investigate liposomal formulations of LA in vivo. To challenge the validity of the model, we tested the motor PNB following an unilamellar liposomal formulation, filled with the intermediate-duration LA lidocaine. Experiments were carried out in adult transgenic mice with fluorescent axons and with fluorescent tagged liposomes to allow in vivo imaging by probe-based confocal laser endomicroscopy. Recovery of conduction following LA injection at the ankle was monitored by stimulation of the tibial nerve fibres at the sciatic notch and recording of the plantar compound motor action potential (CMAP). We detected a delayed recovery in CMAP amplitude following liposomal lidocaine, without detrimental systemic effects. Furthermore, CMAP threshold-tracking studies of the distal tibial nerve showed that the increased rheobase was associated with a sequence of excitability changes similar to those found following non-encapsulated lidocaine PNB in humans, further supporting the translational value of the model.